Digital HR Analytics Capability and Talent Retention: The Mediating Role of Employee Trust in Technology in the Cellular Phone Industry - Elvie Maria; Mulia Sosiady; Kamaruddin Kamaruddin; Poniah Juliawati; Peni Cahyati (Dinasti Publisher, 2026)
The cellular phone industry is characterized by rapid technological innovation, intense competition, and continuous digital transformation. In early 2026, the global smartphone market was dominated by flagship models such as the Apple iPhone 17, Samsung Galaxy S25 Ultra, and Google Pixel 10, while premium performance devices including the OnePlus 15 and Samsung Galaxy Z Fold 7 led in advanced technological capability. In the mid-range and entry-level segments, devices such as Redmi 15C, TECNO Spark 40 Pro+, and Samsung Galaxy A07 gained significant market attention. This dynamic environment requires organizations within the cellular phone industry to strengthen digital human resource strategies to retain high-performing talent. This study examines the effect of Digital HR Analytics Capability on Talent Retention, with Employee Trust in Technology positioned as a mediating variable. This research adopts a quantitative explanatory design using a survey of employees working in companies engaged in the development, production, and distribution of leading smartphone brands in early 2026. Structural Equation Modeling (SEM) was employed to test the direct and indirect relationships among Digital HR Analytics Capability, Employee Trust in Technology, and Talent Retention. The findings indicate that Digital HR Analytics Capability has a positive and significant effect on Employee Trust in Technology. Employee Trust in Technology significantly influences Talent Retention, and Digital HR Analytics Capability also directly affects Talent Retention. Furthermore, Employee Trust in Technology partially mediates the relationship between Digital HR Analytics Capability and Talent Retention. These results suggest that data-driven HR decision-making systems, predictive workforce analytics, and transparent digital performance management enhance employee confidence in technological systems, which in turn strengthens retention intentions. This study contributes to strategic human resource management literature by extending digital capability frameworks into high-technology manufacturing industries. Practically, the findings highlight that companies in the cellular phone industry must not only invest in advanced HR analytics systems but also build employee trust in digital technologies to sustain competitive human capital advantages.